(untitled) (Research, Society and Development, 2022)
Congenital anomalies are developmental disorders of prenatal origin present at birth and can be structural, functional or metabolic. Diagnostic measures, prenatal planning and continuous monitoring are necessary for the early detection of these anomalies, and for that it is necessary to know the epidemiology of such diseases. In view of this, this research aimed to analyze the epidemiological profile of anomalies in live births in the Northeast (2011-2020). An epidemiological, descriptive, quantitative, time series research was carried out with data from SINASC – Information System on Live Births – DATASUS. The data were imported from SINASC into the excel program, where graphs and tables were tabulated and elaborated, then exported to BIOESTAT 5.3, to perform descriptive statistics. The epidemiological profile found showed a majority of: male, brown race, weight (3000g to 3999g) and 5th minute Apgar (8 to 10). The main congenital malformations were musculoskeletal, foot and nervous system deformity. The states of Bahia, Pernambuco, Ceará and Maranhão were the ones with the highest number of records. The mothers are aged between 20 and 29 years, with a low level of education, single, single pregnancy, lasting between 37 and 41 weeks. Prenatal care was performed inappropriately and the type of cesarean delivery. Thus, there is a need to devise new public health strategies to enable pregnant women’s access to prenatal care, which is a challenge for the State, the private sector, educational institutions and civil society as a whole.